GREETING WORDS OF KINSHIP OF KERINCI LANGUAGE IN SIULAK SUB-DISTRICT, KERINCI DISTRICT, JAMBI PROVINCE - Nidde Puspita (Sekolah Tinggi Pariwisata Mataram, 2021)
Language is a means of communication. Through human language, it can convey ideas, thoughts, thoughts and feelings to others. Language is closely related to culture, because language is a part of culture that must be preserved and maintained. Regional languages ​​need special attention, because at present there are so many things that can influence the development of regional languages. One of the regional languages ​​developed in the Indonesian region is Kerinci language. Kerinci language is used as the first language by the Kerinci community in communication using variations according to the cultural context. This type of research is qualitative using descriptive methods. The data in this study are in the form of sentences or words or phrases that contain the greeting words of the Siulak community. Sources of data were obtained from native speakers of the Siulak community in the form of kinship greeting words in the Kerinci language in Siulak sub-district, Kerinci district, Jambi province. The research instrument is the researcher herself. The research location was conducted in Siulak Panjang village, Siulak District. The data analysis phase, namely: (a) transcription or copying, (b) classifying data, (c) data analysis, (d) drawing conclusions. The results of the research found were the form of kinship greeting words based on lineage in Siulak District, Kerinci Regency, Jambi Province are Piyut, Tino, Nyantan, Nduk, Nduk Wo, Nduk cik, Mamak Wo, Mamak ngah, Mamak ndak, Mamak Nek, Mamak Tih, Mamak Tam, Mamak Nsu, Wo, Ngah, Ndak, Nek, Tam, Tih, Nsu. Sebut Nama, Adik, M’pun, Awak, Ka’u, Anak, Nakan, Cucung and Kayo. The words for kinship based on the marriage line in Siulak District, Kerinci Regency, Jambi Province are: Tino, Munyang, Nyantan, Pak, Latung, Pak Wo, Pak Ngah, Pak Ndak, Pak Nek, Pak Tam, Pak Tih, Pak, Mamak Wo, Mamak Ngah, Mamak Ndak, Mamak Nek, Mamak Tam, Mamak Tih,Mamak Nsu, Mamak, Kakak, Nduk Cik, Wo, Ngah, Ndak, Nek, Tam, Putih, Nsu. Sebut Nama, and Kayo.